SELF-EFFICACY, LITERASI KEUANGAN, SOSIAL DAN INVESTASI SAHAM ESG - Alhazami, Lutfi; Rahmawati, Irma (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Environmental, Social, and Governance (ESG)-based stock investment is gaining popularity due to its relevance to sustainability. This research aims to analyze the influence of self-efficacy, financial literacy, and social influence on ESG stock investment decisions among English Literature students at Dian Nusantara University. A quantitative approach was employed in this study, involving 171 respondents selected through purposive sampling. Data were collected using a structured questionnaire and analyzed with multiple linear regression. The research results indicate that all three variables, namely self-efficacy, financial literacy, and social influence, have a positive and significant influence on ESG stock investment decisions. Financial literacy is the most dominant factor in influencing investment decisions. These findings emphasize the importance of developing students' financial competence and self-confidence in supporting wiser and more responsible investment decision-making towards sustainability. In conclusion, this research contributes to understanding the factors influencing young generation's investment preferences towards ESG stocks. These results are important for the development of financial education programs and the promotion of sustainable investment among students.  Keywords: Self-Efficacy Financial Literacy Social Influence ESG Stock Investment Student Investment Decisions Abstrak: Investasi saham berbasis Environmental, Social, and Governance (ESG) semakin diminati karena relevansinya dengan keberlanjutan. Penelitian ini bertujuan untuk menganalisis pengaruh self-efficacy, literasi keuangan, dan pengaruh sosial terhadap keputusan investasi saham ESG di kalangan mahasiswa Sastra Inggris Universitas Dian Nusantara. Pendekatan kuantitatif digunakan dalam penelitian ini, melibatkan 171 responden yang dipilih melalui purposive sampling. Data dikumpulkan menggunakan kuesioner terstruktur dan dianalisis dengan regresi linear berganda. Hasil penelitian menunjukkan bahwa ketiga variabel, yaitu self-efficacy, literasi keuangan, dan pengaruh sosial, memiliki pengaruh positif dan signifikan terhadap keputusan investasi saham ESG. Literasi keuangan menjadi faktor paling dominan dalam memengaruhi keputusan investasi. Temuan ini menekankan pentingnya pengembangan kompetensi keuangan dan kepercayaan diri mahasiswa dalam mendukung pengambilan keputusan investasi yang lebih bijaksana dan bertanggung jawab terhadap keberlanjutan. Kesimpulannya, penelitian ini memberikan kontribusi dalam memahami faktor-faktor yang memengaruhi preferensi investasi generasi muda terhadap saham ESG. Hasil ini penting untuk pengembangan program edukasi keuangan dan promosi investasi berkelanjutan di kalangan mahasiswa. Kata Kunci: Self-Efficacy; Financial Literacy; Social Influence; Investasi Saham ESG; Keputusan Investasi Mahasiswa